2014
DOI: 10.1111/1460-6984.12116
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and behavioural problems in children with language impairments and children with autism spectrum disorders

Abstract: Children with LI and children with ASD in mainstream school show similarly elevated levels of emotional and behavioural problems, which require monitoring and may benefit from intervention. Further work is required to identify the child, family and situational factors that place children with LI and children with ASD at risk of emotional and behavioural problems, and whether these differ between the two groups. This work can then guide the application of evidence-based interventions to these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 38 publications
7
28
0
Order By: Relevance
“…) as shown also by the Social Responsiveness Scale ratings by both parents and teachers in the present research (table ) (see Charman et al . for full details). The parents related these difficulties to the social communication function of language (pragmatic ability) that is a challenge especially for children with ASD but also for a substantial minority of children with LI (Ellis Weismer ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…) as shown also by the Social Responsiveness Scale ratings by both parents and teachers in the present research (table ) (see Charman et al . for full details). The parents related these difficulties to the social communication function of language (pragmatic ability) that is a challenge especially for children with ASD but also for a substantial minority of children with LI (Ellis Weismer ).…”
Section: Discussionmentioning
confidence: 99%
“…,b) and behavioural, emotional and social difficulties (Charman et al . ). The present study examined the parents’ perspectives through individual interviews, whose results could be compared with the individual assessments reported in these accompanying papers and summarized in the present paper.…”
Section: Methodsmentioning
confidence: 97%
“…Language impairment is also associated with sociobehavioral difficulties as indicated by general or aggregated measures across domains, for example, the total difficulties score from the Strengths and Difficulties Questionnaire (Goodman, 1997) -see for example, Charman et al (2015). In addition, more analytical studies have found differentiated risk relative to different aspects of sociobehavioural development.…”
Section: Language Impairment As a Risk Factormentioning
confidence: 99%
“…In addition, more analytical studies have found differentiated risk relative to different aspects of sociobehavioural development. Recent evidence has shown that children with LI are at greater risk than typically developing children especially for academic self-concept, peer problems, and emotional difficulties, whereas conduct problems are less common, although still above the level for typically developing children (Lindsay et al, 2010b;O'Kearney, 2013, 2015;Charman et al, 2015). Furthermore, longitudinal studies have shown that these problems may persist over time St Clair et al, 2011;Lindsay and Dockrell, 2012).…”
Section: Language Impairment As a Risk Factormentioning
confidence: 99%
“…This indicated a substantial overlap as well as differences in degree. For example, levels of peer problems were significantly above the norm for both groups but more so for children with ASD; by contrast, conduct problems, although more prevalent than the norm, were less of a concern (Charman et al., submitted; Lindsay and Dockrell, ). To complement others' views on the difficulties that the children experience, we asked the children about their own quality of life.…”
Section: The Relationship Between Slcn and Besdmentioning
confidence: 95%